Systems of Practice: How Leaders Use Artifacts to Create Professional Community in Schools - Richard R. Halverson (Arizona State University, 2003)
This article explores how local school leaders construct the conditions for professional community in their schools. This paper argues that professional community is a special form of social capital that results, in part, from the design and implementation of facilitating structural networks by instructional leaders in schools. The structural aspects of a school community can be conceived as a system of practice, that is, a network of structures, tasks and traditions that create and facilitate complex webs of practice in organizations. Systems of practice are composed of networks of artifacts, such as policies, programs and procedures, which can be seen as powerful tools used by local leaders to influence local instructional practices. The system of practice framework suggests that leaders use artifacts to establish structures that facilitate the closure of professional networks among teachers, which in turns builds professional community. The leadership practices of an urban elementary school are used to illustrate how professional community has been developed through the selective design and implementation of artifacts in order to reshape the local system of practice.